The impact of mobile phone penetration on African inequality - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
Purpose The aim of this paper is to complement theoretical and qualitative literature with empirical evidence on the income-redistributive effect of mobile phone penetration in 52 African countries. Design/methodology/approach Robust Ordinary Least Squares and Two Stage Least Squares empirical strategies are employed. Findings The findings suggest that mobile penetration is pro-poor, as it has a positive income equality effect. Social implications 'Mobile phone'-oriented poverty reduction channels are discussed. Originality/value It deviates from mainstream country-specific and microeconomic survey-based approaches in the literature and provides the first macroeconomic assessment of the 'mobile phone'-inequality nexus.
Keywords: E00; G20; I30; L96; O33; 330; Mobile Phones; Shadow Economy; Poverty; Inequality; Africa